De novo transcriptome assembly from the gonads of a scleractinian coral, Euphyllia ancora: molecular mechanisms underlying scleractinian gametogenesis - Chiu, Yi-Ling; Shikina, Shinya; Yoshioka, Yuki; Shinzato, Chuya; Chang, Ching-Fong (BMC genomics, 2020)
Sexual reproduction of scleractinians has captured the attention of researchers and the general public for decades. Although extensive ecological data has been acquired, underlying molecular and cellular mechanisms remain largely unknown. In this study, to better understand mechanisms underlying gametogenesis, we isolated ovaries and testes at different developmental phases from a gonochoric coral, Euphyllia ancora, and adopted a transcriptomic approach to reveal sex- and phase-specific gene expression profiles. In particular, we explored genes associated with oocyte development and maturation, spermiogenesis, sperm motility / capacitation, and fertilization. 1.6 billion raw reads were obtained from 24 gonadal samples. De novo assembly of trimmed reads, and elimination of contigs derived from symbiotic dinoflagellates (Symbiodiniaceae) and other organisms yielded a reference E. ancora gonadal transcriptome of 35,802 contigs. Analysis of 4 developmental phases identified 2023 genes that were differentially expressed during oogenesis and 678 during spermatogenesis. In premature/mature ovaries, 631 genes were specifically upregulated, with 538 in mature testes. Upregulated genes included those involved in gametogenesis, gamete maturation, sperm motility / capacitation, and fertilization in other metazoans, including humans. Meanwhile, a large number of genes without homology to sequences in the SWISS-PROT database were also observed among upregulated genes in premature / mature ovaries and mature testes. Our findings show that scleractinian gametogenesis shares many molecular characteristics with that of other metazoans, but it also possesses unique characteristics developed during cnidarian and/or scleractinian evolution. To the best of our knowledge, this study is the first to create a gonadal transcriptome assembly from any scleractinian. This study and associated datasets provide a foundation for future studies regarding gametogenesis and differences between male and female colonies from molecular and cellular perspectives. Furthermore, our transcriptome assembly will be a useful reference for future development of sex-specific and/or stage-specific germ cell markers that can be used in coral aquaculture and ecological studies.